Pemanfaatan Tanaman Obat Keluarga (Toga) di Gampong Surien Kecamatan Meuraxa Banda Aceh - Rina Kurniaty; Rosa Mardiana; Lidyawati; Ria Ceriana; Dwi Putri Rejeki; Sasmiati Farach Dita; Fadli Syahputra (Jurnal Mitra Pengabdian Farmasi, 2021)
This Community dedication was expected to be able to increase the synergy between lecturers and the community in supporting productive Ramadan in Surien village, Meuraxa District, Banda Aceh. Through this service activity, it was expected that it would be able to foster a broader curiosity and made the community independent, creative and innovative in undergoing Ramadan, even though in the midst of increasing cases of COVID-19 in Indonesia and Banda Aceh in particular, by making efforts to generate Community Resilience by socializing the Utilization of Family Medicinal Plants (TOGA), so that the Surien village community was able to use plants and land at home. The implementation of this Community dedication program was carried out in several stages of implementation as follows: Preparation of service protocols, Initial survey of target locations and problems, Meetings with geuchik and village officials, Distributing masks, Socialization the use of Family Medicinal Plants (TOGA), Ramadhan Lectures, ends with Ramadan Donation and preparation of reports. Presentation of the counseling materials was conducted by lecturing using power point slide which contained an explanation of nine types of superior family medicinal plants, as well as by inviting the public to plant TOGA. Community dedication in Surien aimed to unite or to synergize the presence of lecturers with the Surien community in the implementation of Tri Dharma of Higher Education. The success of this community dedication was assessed from the number of participants (75%), the achievement of goals (80%), the achievement of material targets (80%) and the success of planting TOGA at home (80%). The conclusion of this community dedication was that TOGA counseling could increase people's knowledge and understanding of TOGA and the 9 plants that had been clinically tested.